Superhuman with Artificial Intelligence: Classic Ambition Comes to Life - Chandra, Wie Wie (Veritas : Jurnal Teologi dan Pelayanan, 2021)
In his book, 2084: Artificial Intelligence and the Future of Humanity, John Lennox attempts to establish a biblical foundation for the two fundamental and existential problems of humanity, namely, where humans come from and where humans go. His book is divided into 13 chapters. Lennox devotes the first seven chapters to critiquing secular naturalists' responses to these two fundamental problems. He spends the following six chapters demonstrating how Christianity provides specific and more "sophisticated" solutions to the question of man's origin and purpose. Lennox also reminded us that the human goal to utilize technology to overcome natural constraints and become like God is a traditional ambition that has existed since the first human fell into sin. Furthermore, for the purpose of human development, it is frequently exploited as an alibi by a few people who actually desire to reign over nature and the lives of other humans. Lennox advises readers to continue paying attention to motivation and consider the ethical difficulties accompanying every technological advancement. This book is recommended for anyone interested in technological advancement and Christian worldviews.